First Surgical National Consensus Conference of the Italian Breast Surgeons association (ANISC) on breast cancer management in neoadjuvant setting: Results and summary. Issue 8 (August 2021) - De Luca, Alessandro; Frusone, Federico; Buzzacchino, Federica; Amabile, Maria Ida; Taffurelli, Mario; Del Mastro, Lucia; Rutgers, Emiel J.T.; Sacchini, Virgilio; Caruso, Francesco; Minelli, Mauro; Fortunato, Lucio
Abstract: Rationale: On October 15th, 2020, the first Surgical National Consensus Conference on neoadjuvant chemotherapy (NACT) was promoted by the Italian Association of Breast Surgeons (ANISC). Method: The Consensus Conference was entirely held online due to anti-Covid-19 restrictions and after an introductory four lectures held by national and international experts in the field, a total of nine questions were presented and a digital "real-time" voting system was obtained. A consensus was reached if 75% or more of all panelists agreed on a given question. Results: A total of 202 physicians, from 76 different Italian Breast Centers homogeneously distributed throughout the Italian country, participated to the Conference. Most participants were surgeons (75%). Consensus was reached for seven out of the nine considered topics, including management of margins and lymph nodes at surgery, and there was good correspondence between the 32 "Expert Panelists" and the "Participants" to the Conference. Consensus was not achieved regarding the indications to NACT for high-grade luminal-like breast tumors, and the need to perform an axillary lymph node dissection in case of micrometastases in the sentinel lymph node after NACT. Conclusions: NACT is a topic of major interest among surgeons, and there is need to develop shared guidelines. While a Consensus was obtained for most issues presented at this Conference, controversies still exist regarding indications to NACT in luminal B-like tumors and management of lymph node micrometastases. There is need for clinical studies and analysis of large databases to improve our knowledge on this subject. Highlights: Neo-adjuvant chemotherapy (NACT) has been increasingly used in the last two decades, initially with the aim to downstage a locally advanced breast cancer (BC) allowing breast conservative surgery instead of a mastectomy, and to test tumor's chemosensitivity "in vivo". Although in the last few years, other rationales have been suggested to broaden its indications, several controversial issues on this topic still persists. The first Surgical National Consensus Conference on Neoadjuvant Chemotherapy was promoted with the aim to discuss controversial issues and to obtain a "picture of a the current national approach. While a Consensus was obtained for most issues presented at this Conference, controversies exist regarding indications to NACT in luminal B-like tumors and management of lymph node micrometastases. There is need for clinical studies and analysis of large databases to improve our knowledge on this subject.